Individual Community-Based Treatment of Offenders With Mental Illness: Relationship to Recidivism. (June 2016) - Abracen, Jeffrey; Gallo, Alessandra; Looman, Jan; Goodwill, Alasdair
This study explores the effectiveness of psychological intervention at reducing the risk of recidivism among a group of high-risk, high-need offenders housed in a Community Correctional Centre (CCC) operated by the Correctional Service of Canada (CSC). File reviews on 136 male federal offenders living in a CCC in a large metropolitan area were included in the present investigation. Previous research on this sample by our team indicated that the majority of this sample met diagnostic criteria for a variety of psychiatric conditions. Data on the number of individual counseling sessions received and progress in treatment were collected from official file information for the purpose of the present investigation. After accounting for actuarially assessed risk, moderate doses of treatment were found to be associated with 7.7 times less likelihood of recidivism, and high doses of treatment were found to be associated with 11.6 times less likelihood of recidivism, when compared with offenders who received no treatment or were only assessed for treatment. These results are discussed in the context of correctional models of offender risk assessment and rehabilitation. It is notable that a very simple measure of global mental health treatment attendance, with no consideration of such factors as responsiveness, added considerable incremental predictive validity to the results after having statistically accounted for actuarially assessed risk of recidivism.